The Anglo-Germanic and Latin concepts of politeness and time in cross-atlantic business communication: from cultural misunderstanding to management success - Ulijn, Jan M. (HERMES - Journal of Language and Communication in Business, 2017)
Bond and Hofstede (1989) have demonstrated that culture has a large impact on international business success. In Western cultures it would relate to individualism and in Oriental cultures to Confucian dynamism. Their conception of politeness as a leading principle in human relations and their use of time seems unlike that of Western cultures. Within the Western hemisphere, however, Anglo-Germanic and Latin cultures do not share the same concepts of politeness and time. Spanish business letters seem to be overpolite compared to American ones. Whereas Dutch people stick to one topic at the same time in their negotiations, Italians tend to interrupt to tackle as many issues as possible. Anglo-Germanic and Latin cultures seem to differ in their means of expression of politeness in negotiating and writing. The main source seems to be the striking difference in power distance between Anglo-Germanic and Latin management cultures, a phenonomenon which was observed in Hofstede’s first study with IBM (1980). Irrespective of its origin, politeness or the presumed lack of it could easily lead to intercultural misunderstanding. Hofstede’s work can be used as a framework to analyse some of the potential sources of misunderstanding caused by such differences. The purpose of this paper is to summarize some data to illustrate the importance of the above cultures on both sides of the Atlantic Ocean, to evidence some politeness markers including the time concept, such as pausing and silencing in oral communication and courteous beginnings and endings of Latin business letters, and to retrace the perception of such behaviour by a person from the other culture. How can cultures respect each other and how can politeness be interpreted in a proper way without insulting the other party? How can cultures respect each other, learn from each other and cooperate effectively, for instance, in business and technology? What could be the consequences for the international practice of business management and communication in the Anglo-Germanic and Latin cultures of some EU and NAFTA countries? On the basis of those research findings we will present some guidelines for successful intercultural cooperation in the EU keeping an eye on new trade possibilities on the other side of the Atlantic.